PERSETUJUAN PEREMPUAN DALAM PERNIKAHAN: ANTARA MADZHAB SYAFI’I DAN REALITA DI INDONESIA - Sofiana, Neng Eri; Nuraini, Helma (Center of Gender Studies and Child of State Islamic Institute of Metro, 2023)
The Shafi'i school of thought is widely followed in Indonesia, evident in both the framework of the Compilation of Islamic Law (KHI) and Marriage Law No. 1 of 1974, which extensively references the texts of this school. Within the teachings of the Shafi'i madhhab, the approval of women lies in the hands of a guardian or father, even permitting the marriage of women without their consent, except for widows, for whom the consent of the concerned party is required. However, this contrasts with Articles 16 and 17 of the KHI, emphasizing the significance of the consent of all parties involved. Interestingly, this is also supported by on-the-ground realities that prioritize the consent of all parties in conducting marriages, as observed in the Customary Village of Cireundeu, Cimahi City, West Java, and the region of Dalam Pagar Martapura-Hulu Sungai Tengah, South Kalimantan, which allows women to explicitly declare their willingness and consent to marriage. This article aims to examine how the practical application of the Shafi'i madhhab's stance on women's marriage consent aligns with legal frameworks and the observed gender dynamics. The article can be categorized as field research with a qualitative analysis approach, grounded in relevant literature studies related to the discussion.. Ultimately, while the Shafi'i madhhab is widely adopted by the Indonesian populace, it undergoes adaptation to the contemporary circumstances and cultural context in Indonesia, thus representing a synthesis of the Shafi'i madhhab and the indigenous Nusantara traditions. Keywords: Women’s Consent, Syafi’i School in Indonesia, Local Islam.Abstrak Madhzab Syafi’i diketahui banyak diikuti di Indonesia. Begitu pula dalam corak KHI (Kompilasi Hukum Islam) dan Undang-Undang Pernikahan No. 1 Tahun 1974 yang referensinya banyak menggunakan kitab dari madzhab tersebut. Dalam ajaran madzhab Syafi’i, persetujuan perempuan ada di tangan wali atau bapak, bahkan diperbolehkan menikahkan perempuan tanpa seizinnya, kecuali untuk janda, harus ada persetujuan dari yang bersangkutan. Namun berbeda dengan pasal 16 dan 17 KHI yang menegaskan pentingnya persetujuan para pihak. Menariknya, hal ini juga didukung dengan fakta di lapangan yang mengedepankan persetujuan para pihak dalam melaksanakan pernikahan, seperti di Kampung Adat Cireundeu Kota Cimahi Jawa Barat dan daerah Dalam Pagar Martapura-Hulu Sungai Tengah Kalimantan Selatan yang memberi ruang bagi perempuan untuk secara tegas menyatakan diri atas kesediaan dan persetujuannya untuk melakukan pernikahan. Artikel ini akan melihat bagaimana posisi realitas ajaran madzhab Syafi’i tentang persetujuan perempuan menikah pada produk hukum dan realita yang terjadi dalam kacamata gender. Artikel ini dapat dikategorikan sebagai penelitian lapangan dengan analisis kualitatif berdasarkan studi pustaka yang berkaitan dengan pembahasan. Akhirnya, madzhab Syafi’i menjadi madzhab yang banyak dipakai oleh masyarakat Indonesia, namun disesuaikan dengan keadaan zaman dan budaya yang ada di Indonesia itu sendiri, sehingga madzhab Syafi’i yang ada di Indonesia adalah hasil dari ramuan Nusantara. Kata Kunci: Persetujuan Perempuan, Madzhab Syafi’i di Indonesia, Islam lokal.